Global burden of head and neck cancer: Epidemiological transitions, inequities, and projections to 2050 - Sun, Hao; Yu, Mulin; An, Ziyue; Liang, Fangcheng; Sun, Bowen; Liu, Yuanlong; Zhang, Shenquan (Frontiers in Oncology, 2025)
BackgroundHead and neck cancer (HNC) is the seventh most frequently occurring cancer worldwide. The incidence and mortality of HNC have been demonstrated to significantly impact human health and increase the global health burden. We assessed temporal trends via Estimated Annual Percentage Change (EAPC) across 36 countries (2008–2017). No study has yet focused on the latest epidemiological changes of GLOBOCAN 2022 in HNC and made predictions about the trends to 2050.ObjectivesIntegrate historical HNC records and project global incidence and mortality trends to 2050 to support region-specific prevention strategies.MethodsData on HNC cases and deaths including rates for subtypes were gathered from GLOBOCAN 2022 (https://gco.iarc.fr). The age-standardized incidence and mortality rates per 100,000 person-years were calculated by the direct age standardization method based on the Segi-Doll World standard population. We counted EAPC in 36 countries over the last decade (2008-2017). Eight of these countries with different levels of development were also selected to observe in detail their annual trends from 1980 to 2017. Relationship between the Human Development Index (HDI) and the HNC subtypes was examined using linear regression.ConclusionFrom 2008 to 2017, both the number of male HNC deaths and cases decreased. However, in 2022, the men’s and older people’s HNC burden is still heavier. According to the projection, future reductions in overall HNC incidence and mortality are expected to materialize only in the event of a decline in cases and deaths by 2 or 3 percent or more.